Acute promyelocytic leukemia (APL) in very old patients: real-life behind protocols. (2nd November 2021) - Rosati, Serena; Gurnari, Carmelo; Breccia, Massimo; Carmosino, Ida; Scalzulli, Emilia; Montefusco, Enrico; Perrone, Salvatore; Annibali, Ombretta; Martini, Vincenza; Trapè, Giulio; Colafigli, Gioia; Trawinska, Malgorzata; et al.
Abstract: Background: Acute promyelocytic leukemia (APL) is uncommon among subjects aged ≥ 70 years and the better therapeutic strategy represents an unmet clinical need. Materials and methods: This prompted us to explore our real-life data on a retrospective cohort of 45 older APL patients (≥ 70 years) consecutively diagnosed at eight different hematologic institutions in Latium, Italy, from July 1991 to May 2019. Results: Two patients (4.4%) died from early hemorrhagic complications before treatment could begin. Twenty-two patients (51.1%) (Group A) were enrolled or treated according to standard clinical protocols, while 21 (48.8%) (Group B) received an ATRA-based personalized approach due to poor performance status. Morphologic complete remission (CR) after induction therapy was achieved in 33 patients (76.7%) with 100% of patients in Group A and 52.3% in Group B ( p  < 0.001). Molecular CR was documented in 30 patients (69.7%) [20/22 (90.9%) in Group A and 10/21 (47.6%) in Group B ( p  = 0.002)]. Ten patients (23.2%) died during induction therapy, all in Group B. Five-year overall survival (OS) of the entire cohort was 46.1% (95% CI 28.2–64.0), with 72.6% (95% CI 42.9–100) in Group A vs. 27.2% (95% CI 7.5–46.9) in the Group B ( p  = 0.001). Conclusions: The present analysis highlights that almost half of the patients received sub-optimal induction treatments and registered dismal outcomes demonstrating the importance of adopting standard therapies instead of modified or reduced personalized approaches also in the setting of frail older patients.